Del Águila Peralta, Alicia. La ciudadanía corporativa. Política, constituciones y sufragio en el Perú (1821-1896). Lima: Instituto de Estudios Peruanos, 2013, xxx + 319 pp. - Sobrevilla Perea, Natalia (2014)
No presenta resumen